Observation and quantification of three-dimensional crack propagation in poly-granular graphite - Mostafavi, M; McDonald, SA; Mummery, P; Marrow, T (Elsevier, 2013)
Observations of fracture are generally restricted to the surface of test specimens; yet the fracture process occurs within the material. X-ray computed tomography (XCT) provides valuable insights into the structures within materials: when XCT is combined with digital volume correlation (DVC) the response to applied loads can be measured with high precision in the form of the three-dimensional displacement field within the material. This paper reports a study of the fracture behaviour of a short-bar chevron notch crack propagation specimen fabricated from polygranular nuclear graphite - a quasi-brittle material. A three-dimensional linear elastic finite element simulation of the specimen obtained the relations between crack length, opening displacement and stress intensity factor along the crack front. Tomographic absorption contrast images were obtained from the specimen before and after crack propagation, whilst loaded. The DVC-measured displacement field was used to measure and map the crack opening displacements in 3D; the experimentally calculated crack opening displacements were consistent with the FE-predicted values. The measurements demonstrate the existence of a cohesive fracture process zone ahead of the crack tip, which is a characteristic of quasi-brittle materials. This suggests that simulation of the fracture of non-irradiated polygranular nuclear graphite requires a material model capable of showing softening behaviour. Copyright 2013 Elsevier Ltd. All rights reserved.